Deficiency for the Chemokine Monocyte Chemoattractant Protein-1 Aggravates Tubular Damage after Renal Ischemia/Reperfusion Injury - Stroo, Ingrid; Claessen, Nike; Teske, Gwendoline J. D.; Butter, Loes M.; Florquin, Sandrine; Leemans, Jaklien C. (PloS one, 2015)
Temporal expression of chemokines is a crucial factor in the regulation of renal ischemia/reperfusion (I/R) injury and repair. Beside their role in the migration and activation of inflammatory cells to sites of injury, chemokines are also involved in other processes such as angiogenesis, development and migration of stem cells. In the present study we investigated the role of the chemokine MCP-1 (monocyte chemoattractant protein-1 or CCL2), the main chemoattractant for monocytes, during renal I/R injury. MCP-1 expression peaks several days after inducing renal I/R injury coinciding with macrophage accumulation. However, MCP-1 deficient mice had a significant decreased survival and increased renal damage within the first two days, i.e. the acute inflammatory response, after renal I/R injury with no evidence of altered macrophage accumulation. Kidneys and primary tubular epithelial cells from MCP-1 deficient mice showed increased apoptosis after ischemia. Taken together, MCP-1 protects the kidney during the acute inflammatory response following renal I/R injury.